2020
DOI: 10.3390/nu12051426
|View full text |Cite
|
Sign up to set email alerts
|

Defatted Tenebrio molitor Larva Fermentation Extract Modifies Steatosis, Inflammation and Intestinal Microflora in Chronic Alcohol-Fed Rats

Abstract: This study examined the effects of defatted mealworm fermentation extract (MWF) on alcoholic liver injury in rats. The rats were fed either a Lieber-DeCarli control (Con) or alcohol liquid diet (EtOH). The alcohol-fed rats were administered MWF (50, 100, or 200 mg/kg/day) and silymarin (200 mg/kg/day) orally for eight weeks. MWF prevented alcohol-induced hepatocellular damage by decreasing their serum aspartate transaminase, alanine transaminase, and gamma-glutamyl transpeptidase levels significantly compared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 58 publications
2
21
0
Order By: Relevance
“…A recent study reported that defatted TMP (200 mg/kg body weight, oral supplementation) prevented alcoholic hepatic steatosis in rats by regulating de novo TG and cholesterol synthesis [ 12 ]. It had a higher amino acid content than the non-fermented extract.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent study reported that defatted TMP (200 mg/kg body weight, oral supplementation) prevented alcoholic hepatic steatosis in rats by regulating de novo TG and cholesterol synthesis [ 12 ]. It had a higher amino acid content than the non-fermented extract.…”
Section: Discussionmentioning
confidence: 99%
“…Preparation of TMP was as described in a previous study [ 12 ]. Defatted and freeze-dried powder was fermented for 72 h using a Saccharomyces cerevisiae strain (KCTC 17299, Korean Cell Line Bank, Seoul, Korea).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Cho et al [7] reported that yellow mealworm alcalase hydrolysates protected AML12 mouse liver cells against reactive oxygen species. Our previous study showed for the first time that defatted mealworm fermentation extract (MWF) might attenuate alcohol-induced liver injury by regulating the lipogenic and inflammatory pathways and the antioxidant defense system and by partially altering gut microbial composition [8].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, in this study, target metabolome studies on serum AAs, OAs, and FFAs were performed by profiling, star pattern recognition, and multivariate analyses to assess hepatoprotective effects of MWF against the development of alcoholic steatosis in the ALD rat model. We have integrated the results of this metabolic profiling and previous molecular mechanism analyses [8], providing an improved understanding for the protective effects of MWF on chronic alcohol-induced liver injury.…”
Section: Introductionmentioning
confidence: 99%